Measuring Height Change Around the Periphery of the Greenland Ice Sheet With Radar Altimetry - Gray, Laurence; Burgess, David; Copland, Luke; Langley, Kirsty; Gogineni, Prasad; Paden, John; Leuschen, Carl; van As, Dirk; Fausto, Robert; Joughin, Ian; Smith, Ben (Frontiers in Earth Science, 2019)
Ice loss measurements around the periphery of the Greenland Ice Sheet can provide key information on the response to climate change. Here we use the excellent spatial and temporal coverage provided by the European Space Agency (ESA) CryoSat satellite, together with NASA airborne Operation IceBridge and automatic weather station data, to study the influence of changing conditions on the bias between the height estimated by the satellite radar altimeter and the ice sheet surface. Surface and near-surface conditions on the ice sheet periphery change with season and geographic position in a way that affects the returned altimeter waveform and can therefore affect the estimate of the surface height derived from the waveform. Notwithstanding the possibility of a varying bias between the derived and real surface, for the lower accumulation regions in the western and northern ice sheet periphery (< ~1 m snow accumulation yearly) we show that the CryoSat altimeter can measure height change throughout the year, including that associated with ice dynamics, summer melt and winter accumulation. Further, over the 9-year CryoSat lifetime it is also possible to relate height change to change in speed of large outlet glaciers, for example, there is significant height loss upstream of two branches of the Upernavik glacier in NW Greenland that increased in speed during this time, but much less height loss over a third branch that slowed in the same time period. In contrast to the west and north, winter snow accumulation in the south-east periphery can be 2 - 3 m and the average altimeter height for this area can decrease by up to 2 m during the fall and winter when the change in the surface elevation is much smaller. We show that vertical downward movement of the dense layer from the last summer melt coupled with overlying dry snow, are responsible for the anomalous altimeter height change. However, it is still possible to estimate year-to-year height change measurements in this area by using data from the late-summer to early-fall when surface returns dominate the altimeter signal.